(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The concept of independent learning is essential for developing the necessary competencies for students in professional activities. This study explores how independent learning methods can be integrated into professional development programs, enhancing students’ problem-solving skills, critical thinking, and autonomous decision-making. A methodological framework for guiding students towards becoming self-sufficient learners within their chosen professions is proposed. This research focuses on the pedagogical foundations of independent learning and its significance in professional training.